SAEB Context Questionnaries: Based Qualitative Analysis in the Factorial Analysis Results - Raíssa Rauter; Jacob Arie Laros; Girlene Ribeiro de Jesus (Universidad Autónoma de Madrid, 2018)
The present study focuses on the psychometric quality of the questions related to school characteristics of the questionnaires of the National Basic Education Evaluation System (SAEB) in Brazil. These instruments are an important source of information regarding which variables are associated with student achievement. Factor analysis of the 163 questions related to school of the SAEB 2001 questionnaires applied to 4th grade students revealed a factorial structure with 19 first order factors and 5 second order factors. Only 83 of the 163 questions (51%) could be included in the final factor model. Content analysis of the questions not included in the factor model indicated as a possible reason of exclusion the lack of one or more of the following attributes: simplicity, precision, relevance and clarity. The results of this study will hopefully contribute to an improvement of the SAEB questionnaires and to a more precise assessment of the school factors associated with student achievement in Brazil